Deciphering the Roles of Molecular Weight and Carboxyl Richness of Organic Matter on Their Adsorption onto Ferrihydrite Nanoparticles and the Resulting Aggregation - Li, Zhixiong; Stacey M. Louie; Juntao Zhao; Juanjuan Liu; Jing Zhang; Chen, Jiawei*; Huazhang Zhao; Yandi* Hu (Environmental Science & Technology, 2024)
The aggregation behavior of ferrihydrite nanoparticles (FNPs) can control the fate of associated aqueous contaminants, trace elements, and organic compounds. However, FNP aggregation is difficult to predict in the presence of organic matter (OM), given the heterogeneity in the OM properties. Five model OMs based on (poly)acrylic acid (PAA or AA) and polyethylene glycol with or without terminal carboxyl groups (PEG or PEGbis, respectively) were chosen to probe the influence of key OM properties─specifically, carboxyl richness and molecular weight (MW)─and the dominant mechanisms by which they influence OM adsorption onto FNPs and the resulting aggregation. For OMs with similar MWs, those with a higher carboxyl richness adsorbed more extensively onto FNPs: PAA2k > PEGbis > PEG. Meanwhile, for OMs with the same carboxyl richness, higher MW OMs adsorbed more: PAA25k > PAA2k > AA. Furthermore, the subsequent aggregation of FNPs was largely controlled by the adsorbed mass. OMs with negligible adsorption (i.e., PEG and AA) did not change the aggregation behavior of FNPs. For OMs with low carboxyl richness (PEGbis), accelerated aggregation occurred through a bridging effect with low adsorbed mass. For OMs with high carboxyl richness (PAA2k and PAA25k), aggregation was accelerated at moderate adsorbed OM masses by patch-charge attraction and was inhibited with high adsorbed OM mass due to steric repulsion. This study provided new insights into understanding and predicting the transport and fate of FNPs and natural organic matter (NOM) in natural environments with various NOM compositions.